Readiness of Makassar Public High School Counsellors in Coping Organizational Change - Andi Dasmawati; Yusof Boon (Journal of Education and Learning (EduLearn), 2014)
This study aims to determine the readiness of State High School counsellors in the city of Makassar who are confronted with organizational change. The assessment is viewed from the aspect of preparedness of counsellors that includes self-esteem, optimism and perceived control. A mixed method was used in this study that was simultaneously embedded. Survey questionnaires were distributed to 68 counsellors of State High Schools in Makassar for purposes of quantitative analysis, while an interview was conducted to five counsellor-coordinators for purposes of qualitative analysis.Â  Both descriptive and inferential statistics were employed to best analyze the quantitative data, while the qualitative data was analyzed manually. The study revealed that the level of readiness of the 68 counsellorsâ€™ performance was low in coping with organizational change. This implies that there is a need for the counsellors to improve their performance in the future. Through the qualitative analysis, it was found out that the counsellors have numerous difficulties in their ability to cope with organizational change, while the result of good performance was noted in the quantitative analysis that was conducted.